Study on the Hydrogen Charging and Dehydrogenation Behavior ofTypical Materials in Hydrogen System - XU Shu-jian, LIU Xiao-hui, QU Ding-rong, QIU Zhi-gang, XU Ke (Cailiao Baohu, 2021)
For providing a certain technical guidance for constant temperature dehydrogenation operation during the shutdown process of the hydrogenation unit, the experiments of hydrogen charging and dehydrogenation of seven typical materials were carried out to measure the changes of mechanical properties of materials before and after hydrogen charging, observe the changes of microstructure and fracture morphology of materials before and after hydrogen charging, and determine the hydrogen permeation state by calculating the hydrogen diffusion coefficient in room temperature and measuring the hydrogen content under different dehydrogenation processes. Meanwhile, the computer simulation of dehydrogenation of carbon steel and stainless steel at different temperatures was carried out to study the variation of hydrogen evolution curves of carbon steel and stainless steel with changing temperature. Based on the above experiments and computer simulations, the harmfulness of hydrogen permeation of materials was revealed, and the necessity of constant temperature dehydrogenation was verified.